2018
DOI: 10.1016/j.humpath.2017.12.005
|View full text |Cite
|
Sign up to set email alerts
|

The selected biomarker analysis in 5 types of uterine smooth muscle tumors

Abstract: Uterine smooth muscle tumors (USMTs) consist of a group of histologically heterogeneous and clinically diverse diseases ranging from malignant leiomyosarcoma (LMS) to benign leiomyoma (ULM). The genetic alterations in LMS are complex, with some genetic alterations present in both LMS and other atypical histologic variants of USMT. In this study, we reviewed 119 USMTs with a diagnosis of LMS, smooth muscle tumor of uncertain malignant potential, atypical leiomyomas/leiomyoma with bizarre nuclei, and cellular le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 30 publications
6
19
0
Order By: Relevance
“…In fact, high PR expression has a statistically significant association with longer overall survival, thereby providing useful prognostic data. These results suggest that PR positivity may represent a positive prognostic factor for recurrence and survival in LMS, similarly to previously published data (29)(30)(31).…”
Section: Immunohistochemical Patternssupporting
confidence: 91%
See 3 more Smart Citations
“…In fact, high PR expression has a statistically significant association with longer overall survival, thereby providing useful prognostic data. These results suggest that PR positivity may represent a positive prognostic factor for recurrence and survival in LMS, similarly to previously published data (29)(30)(31).…”
Section: Immunohistochemical Patternssupporting
confidence: 91%
“…These findings were recently confirmed by Zhang et al (30). In their study, 119 cases of uterine smooth-muscle tumors were reviewed, including LMS, LM and STUMP.…”
Section: Immunohistochemical Patternssupporting
confidence: 54%
See 2 more Smart Citations
“…Furthermore, high PR expression was significantly associated with longer overall survival. 20 In the current study, 75% of STUMP tumors (12/16) showed PR expression and 63% (10/16) showed ER expression. The recurrent case showed 30% Ki-67 and was negative for p53 and positive for PR and ER.…”
Section: Discussionsupporting
confidence: 48%